2004
DOI: 10.1016/j.amjhyper.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness is greater in African Americans than in whites evidence from the Forsyth County, North Carolina, ARIC cohort

Abstract: This report on arterial mechanics in African Americans suggests that large artery stiffening either occurs earlier, or is more accelerated in African Americans than in whites in our sample, perhaps as a result of earlier exposure to multiple risk factors. This finding may have implications for hypertension prevention, as arterial stiffness is associated with the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 34 publications
9
55
0
2
Order By: Relevance
“…The higher PP found among African descent populations in this study is consistent with the higher PP reported among African Americans in the USA. [33][34][35] The WMD in PP was more pronounced in women than in men of African descent in this study. The higher BMI in African descent women may partly contribute to their higher PP.…”
Section: Discussion Of Key Findingsmentioning
confidence: 63%
“…The higher PP found among African descent populations in this study is consistent with the higher PP reported among African Americans in the USA. [33][34][35] The WMD in PP was more pronounced in women than in men of African descent in this study. The higher BMI in African descent women may partly contribute to their higher PP.…”
Section: Discussion Of Key Findingsmentioning
confidence: 63%
“…In fact, some studies have shown that black individuals have higher cf‐PWV values than their white counterparts 14, 15. Other studies, however, did not find this difference 16, 17.…”
Section: Introductionmentioning
confidence: 93%
“…98 -100 Similarly, greater intima-media thickening of large resistance vessels, such as the carotid artery, has also been documented. 101 Functional vascular abnormalities occurring more often in blacks than in whites include greater stiffness of large central arteries 97,102 and a lesser capacity of resistance vessels to dilate in response to vasodilatory stimuli. 98,99 These abnormalities in resistance vessels have further been linked to greater pressure-related target-organ injury in blacks.…”
Section: Functional and Anatomic Vascular Abnormalitiesmentioning
confidence: 99%
“…96,97 The abnormalities in the arterial vasculature are substantive but nonspecific and relate to both impaired endotheliumdependent and endothelium-independent vascular function. 98 -100 Similarly, greater intima-media thickening of large resistance vessels, such as the carotid artery, has also been documented.…”
Section: Functional and Anatomic Vascular Abnormalitiesmentioning
confidence: 99%